Day 3 Wed, September 26, 2018 2018
DOI: 10.2118/191673-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Viability of Gas Injection EOR in Eagle Ford Shale Reservoirs

Abstract: Gas Injection, Huff-and-Puff Enhanced Oil Recovery (EOR) technique have the potential to improve liquid hydrocarbon recovery in ultra-tight, unconventional reservoirs. This paper studies the technical and economic viability of this EOR technique in Eagle Ford shale reservoirs using natural gas injection – generally after some period of primary depletion, typically through long horizontal reach wells that were hydraulically fractured. To achieve this, three primary steps were undertaken: First, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is particularly dangerous when the high rate of hydrogen injection and withdrawal is implemented, which would further lead to plastic irreversible reservoir deformation and compromise storage integrity [179,235]. The deformation of reservoirs triggered by cyclical stress alteration may also cause reservoir compaction, decreasing formation porosity and hydrogen cycling efficiency [236][237][238]. For the caprock, hydrogen cycling associated stress regime change can weaken the sealing capacity by causing tensile and shear damage [177,179,239].…”
Section: Hydrogen Cyclingmentioning
confidence: 99%
“…This is particularly dangerous when the high rate of hydrogen injection and withdrawal is implemented, which would further lead to plastic irreversible reservoir deformation and compromise storage integrity [179,235]. The deformation of reservoirs triggered by cyclical stress alteration may also cause reservoir compaction, decreasing formation porosity and hydrogen cycling efficiency [236][237][238]. For the caprock, hydrogen cycling associated stress regime change can weaken the sealing capacity by causing tensile and shear damage [177,179,239].…”
Section: Hydrogen Cyclingmentioning
confidence: 99%
“…However, a long shut-in period would result in a shorter production time. The optimum soaking time can be determined by calculating the gross/net gas utilization [7], as well as associating the cycle numbers and pressure distribution [36]. Some experimental and simulation results indicated that at miscible CO 2 injection condition, a longer soaking period allowed gas to diffuse further into the matrix, leading to a higher accumulative recovery [7,31,32].…”
Section: Sensitivity Analysismentioning
confidence: 99%